Treatment- and immune-related adverse events of immune checkpoint inhibitors in esophageal or gastroesophageal junction cancer: A network meta-analysis of randomized controlled trials - Zheng, Jianqing; Huang, Bifen; Xiao, Lihua; Wu, Min; Li, Jiancheng (Frontiers in Oncology, 2022)
Objective: To systematically evaluate the safety and adverse-event profiles of immune checkpoint inhibitors (ICIs) in patients with esophageal cancer (EPC) or gastro-esophageal junction cancer (GEJC). Methods: PubMed, Web of Science, Cochrane library and major conference proceedings were systematically searched for all phase II or phase III randomized controlled trials (RCTs) in EPC or GEJC using ICIs. Safety outcomes including treatment-related adverse events (trAEs), immune-related adverse events (irAEs), serious trAEs were evaluated by network meta-analysis or dichotomous meta-analysis based on random-effect model. Results: 11 RCTs involving EPC (5 RCTs) and GEJC (6 RCTs) were enrolled in the final meta-analysis. NMA showed that placebo was associated with the best safety ranking for grade 3-5 trAEs (SUCRA=96.0%), followed by avelumab (78.6%), nivolumab (73.9%), ipilimumab (57.0%) and pembrolizumab (56.6%). Conventional pairwise meta-analysis (CPM) showed that ICIs has similar grade 3-5 trAEs risk compared with chemotherapy (RR = 0.764, 95%CI: 0.574 to 1.016, I2 = 95.7%, Z =1.85, P = 0.065). NMA showed that the general safety of grade 3-5 irAEs ranked from high to low are: ChT (85.1%), placebo (76.5%), ipilimumab (56.0%), nivolumab (48.5%), avelumab (48.4%), camrelizumab (41.8%), pembrolizumab (36.4%) and nivolumab + ipilimumab (21.6%). CPM showed that the rates of grade 3-5 irAEs in the ICIs group and the chemotherapy group were 7.35% (154/2095, 95%CI: [6.23%, 8.47%]) versus 2.25% (42/1869, 95%CI: [1.58%, 2.92%]), with statistical significance (RR=3.151, 95% CI=2.175 to 4.563, Z=6.07, P= 0.000). The most common irAEs in the ICIs group were skin reaction (15.76%, 95%CI: [13.67%, 17.84%]), followed by hypothyroidism (9.73%, 95%CI: [8.07%, 11.39%]), infusion-related reactions (5.93%, 95%CI: [4.29%, 7.58%]), hepatitis (5.25%, 95%CI: [4.28%, 6.22%]) and pneumonitis (4.45%, 95%CI: [3.5%, 5.4%]). Conclusion: Different ICIs had different toxicity manifestations and should not be considered as an entity. Compared with chemotherapy, ICIs were more prone to irAEs, but the overall rates remained low and acceptable. For clinicians, it was important to to recognize and monitor the adverse events caused by ICIs for patients with EPC or GEJC.